REFORMASI KINERJA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA MALANG - Muhammad Fadil; Busyra Nur; M Ikhsanul Jihad; Zaenal Abidin (Universitas Diponegoro, 2020)
Public services become one of the obligations that must be done by the government, public services in the administrative field often have some problems such as delays in administrative management until the failure to run the bureaucracy there in, Therefore good governance is present in answering the problem by noble bureaucratic reform of the government. Often administrative problems arise due to problems of productivity, discipline, and effectiveness. Some administrative problems arise in some areas in Indonesia as well as in the city of Malang on the Civil Registration service of the city of Malang. The reform of the Government's Civil service is in institutional aspects by streamlined the organizational structure and changes in service procedures to maximize the provision of services to the community. In the workmanship that is still experiencing obstacles such as inadequate human resources therefore the reform is a fundamental effort to make changes in the direction of the better in terms of input and output bureaucracy related. In the process, the civil registration service of the city of Malang applies several things to bring bureaucracy reform.